2009
DOI: 10.1096/fj.08-128579
|View full text |Cite
|
Sign up to set email alerts
|

Common micro‐RNA signature in skeletal muscle damage and regeneration induced by Duchenne muscular dystrophy and acute ischemia

Abstract: The aim of this work was to identify micro-RNAs (miRNAs) involved in the pathological pathways activated in skeletal muscle damage and regeneration by both dystrophin absence and acute ischemia. Eleven miRNAs were deregulated both in MDX mice and in Duchenne muscular dystrophy patients (DMD signature). Therapeutic interventions ameliorating the mdx-phenotype rescued DMD-signature alterations. The significance of DMD-signature changes was characterized using a damage/regeneration mouse model of hind-limb ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
263
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(287 citation statements)
references
References 32 publications
19
263
0
5
Order By: Relevance
“…miRNA profiles of different skeletal muscle disorders (16)(17)(18)(19)(20)(21) revealed that, despite their heterogeneity, these disorders share a common set of deregulated miRNAs, which generally includes myomiRs.…”
Section: Micrornasmentioning
confidence: 99%
“…miRNA profiles of different skeletal muscle disorders (16)(17)(18)(19)(20)(21) revealed that, despite their heterogeneity, these disorders share a common set of deregulated miRNAs, which generally includes myomiRs.…”
Section: Micrornasmentioning
confidence: 99%
“…miRNAs are emerging as important regulators of muscle development, homeo-stasis and regeneration, and several studies reported on altered levels of miRNAs in muscular dystrophies and other muscular disorders (56,57). A number of muscle-specific and nonspecific miRNAs are induced during myogenesis, and many genes controlling myoblast proliferation and differentiation are the targets of miRNAs (58).…”
Section: Intracellular Conversion Of External Cues Into the Epigenetimentioning
confidence: 99%
“…MiRNAs are from 17 to 24 nucleotides in length and are known to interact with 39-untranslated regions (39 UTRs) of target mRNAs, resulting in the repression of mRNA translation and/or stability (Bartel, 2004). Since miRNAs can repress multiple target mRNAs, miRNA expression patterns and their predicted target mRNAs might represent a novel regulatory network (Eisenberg et al, 2007;Greco et al, 2009;Williams et al, 2009). MiRNAs are involved in the process of regeneration and hypertrophy/atrophy in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%